Absolute annual incidences of first events of venous thromboembolism and arterial vascular events in individuals with elevated FVIII:c - Bank, Ivan; van de Poel, Marlène H. W.; Coppens, Michiel; Hamulyák, Karly; Prins, Martin H.; van der Meer, Jan; Veeger, Nic J. G. M.; Büller, Harry R.; Middeldorp, Saskia (Thrombosis and Haemostasis, 2007)
Elevated levels of factor VIII:c (elevated FVIII:c) are associated with an increased risk for venous thromboembolism (VTE) and arterial vascular events, and are at least in part determined genetically. We prospectively followed 192 asymptomatic individuals with elevated FVIII:c (>150%) and 340 with normal levels for an average duration of 31 months (range 7 to 56 months) to investigate the risk of VTE and arterial vascular events. Participants were first degree relatives of consecutive patients with elevated FVIII:c and VTE or arterial vascular events before the age of 50 years. The incidences ofVTE were 1.25% (0.46–2.73) per year in the subjects with elevated FVIII:c, versus 0.23% (0.03–0.82) in those with normal levels (OR 5.5 [1.1–27.3]). The annual incidences of arterial vascular events were 1.04% (0.34–2.42) and 0.23% (0.03–0.82) in relatives with and without elevated levels of FVIII:c, respectively (OR: 4.5 [0.9–23.5]). After adjustment for age, smoking, known diabetes mellitus, hyperlipidemia, and hypertension, the odds ratio for any event was 3.7 (1.1–13.1). In conclusion, asymptomatic individuals with elevated FVIII:c levels and a positive family history of VTE or arterial vascular events before the age of 50 appear to have a high annual incidence of first VTE and arterial vascular events. Elevated FVIII:c may be a common risk factor for both clinical entities.
Keywords: Elevated FVIII:c; venous thromboembolism; arterial vascular events; family cohort study